The Influence of Study Time and Calculus Course Lecturers on Student Learning Outcomes - Fajarwati, Septi; Rakhmawati, Desty (Jurnal Pendidikan Edutama, 2025)
This study aims to analyze the influence of study time and lecturer competence on the learning outcomes of Informatics students at Universitas Amikom Purwokerto. The method used in this research is quantitative with a survey approach and statistical analysis. The sample consisted of 64 students who had completed the Calculus course in the 2022/2023 academic year. Data were collected from the students' final grades and analyzed using multiple linear regression tests. The analysis results indicated no significant influence between study time (morning and afternoon) and lecturer competence on student learning outcomes, both simultaneously and individually. The F-test and t-test results demonstrated that both independent variables were insignificant in influencing student learning outcomes. Therefore, it can be concluded that study time and lecturer competence statistically do not significantly contribute to students' academic achievement in the Calculus course. This research suggests that other factors, such as teaching methods and student motivation, may play a more crucial role in determining academic success.